APLIKASI RESEP MAKANAN UNTUK PENDERITA DIABETES MENGGUNAKAN CASE BASED REASONING (Information Technology and Telematics, 2015)
Abstract One of diabetics problems is difficult to run a low-sugar diet. Lots of people with diabetes mellitus who are still carelessly in eating food. So that it will only make matters worse. To get the solutions to these problems takes an expert who is expert in his field. But, to connect with experts wasn’t without problems. Experts can’t be found anytime, and expensive cost to undertake consultation is also an issue that must be considered. From the problems described above, it is concluded that we need an application of healthy recipes for diabetics with its ingredients and how to make the recipes. This application is intended for people with diabetes so that they can be succeed to run a low-sugar diet in order to control blood sugar levels without losing an opportunity to enjoy different types of delicious cuisine. This application can’t only be accessed using a computer but it can also be accessed using a mobile device. In finding a recipes solution, the author using the Nearest Neighbor algorithm, which compares existing parameter of weight similarity in the new case with the overall number of parameters in the ever-before cases. This application contains 60 healthy recipes that can be used by public especially diabetics as a guidance in order to keep a healthy life. Keyword : Case Base Reasoning, Diabetes Mellitus, Healthy food